Preterm Infant's Heart Rate Variability Near Birth Predicts Autonomic Symptoms at Age 3 to 5 Years - Zohar, Noa; Katz-Leurer, Michal; Zuk, Luba; Israeli-Mendlovic, Hadas (American Journal of Perinatology Reports, 2024)
Aims To describe the autonomic function of premature infants born between 28 and 32 weeks of gestation, without medical risk factors, at the age of 3 to 5 years and to assess whether it's possible to predict the appearance of autonomic deficits in these children at this age range.Methods This follow-up study included 40 out of 55 premature infants born between weeks 28 and 32 during 2018 to 2020. During 2022 to 2023 parents were asked to report on medical and developmental follow-up and treatment, functional characteristics of the autonomic system, and the age at which walking was achieved.Results Approximately 27% of the participants (11 out of 40) presented autonomic symptoms at 3 to 5 years of age. A predictive relationship was noted between the function of the heart rate control system near birth and the presence of autonomic dysfunctions at ages 3 to 5. Fourteen of 40 children received neurodevelopmental treatments. However, children with autonomic symptoms were not treated for their symptoms.Conclusion These preliminary findings provide valuable insights into the autonomic function of children born premature and the potential predictive relationship between early autonomic measures and later autonomic dysfunctions. It also highlights the need for increased awareness and intervention strategies for addressing autonomic issues in premature infants to support their overall well-being.
Keywords: preterm; autonomic symptoms; follow-up; heart rate variability